(Z)-7, 4'-Dimethoxy-6-hydroxy-aurone-4-O-β-glucopyranoside mitigates retinal degeneration in Rd10 mouse model through inhibiting oxidative stress and inflammatory responses. (2nd January 2020) - Chen, You; Yang, Ming; Wang, Zhi-Jun
Abstract: Purpose: As an inherited retinal dystrophy characterised by progressive degeneration of photoreceptor cells, retinitis pigmentosa (RP) leads to partial or total blindness eventually. Possible causes of the photoreceptor cell death are oxidative stress and inflammatory responses. (Z)-7, 4'-Dimethoxy-6-hydroxy-aurone-4-O-β-glucopyranoside (DHAG) is a novel compound with potent antioxidant properties. The aim of this study was to investigate whether DHAG could mitigate photoreceptor cell degeneration in an established mouse model of RP. Materials and method: Rd10 mice were treated with DHAG daily by gavage from postnatal day 12 (P12) to P33. Retinal morphology was evaluated by haematoxylin and eosin staining. Apoptosis-positive cells were detected by terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL) assay. Oxidative stress markers and inflammatory factors were measured by enzyme-linked immunosorbent assay (ELISA). Real-time polymerase chain reaction, immunostaining and western blot were applied to measure the gene and protein change to explore the underlying mechanisms. Results: Results showed that DHAG significantly preserved the retinal morphology, reducing photoreceptor cell apoptosis, decreasing oxidative stress and inhibiting inflammatory responses in Rd10 mice. The mechanism might be related to inhibit the activation of P38 pathway. Conclusions: This study showed the beneficial effects of DHAG, a compound possessing antioxidant properties, and provided scientific rationale to develop DHAG as a potential agent to treat RP.